Factors contributing to the organizational success: a study on Airasia Berhad / Zurawati Yazid, Norhazwanie Sudin and Tengku Nur Puteri Khairunisa Tengku Zainul Muluk - Yazid, Zurawati; Sudin, Norhazwanie; Tengku Zainul Muluk, Tengku Nur Puteri Khairunisa (Arshad Ayub Graduate Business School, 2018)
The purpose of this paper is to identify organization success factors that contributed to the organizational success on Air Asia Berhad. In addition, this study also examined the relationships between the organization success factors which are leadership, organizational culture, reward and recognition, employee engagement and performance management on the successful performance of Air Asia Berhad. Furthermore, strategy that can enhance the successful performance of Air Asia Berhad are recommended. This study used a cross sectional survey research design using a quantitative approach. The population of this study are employees of Air Asia Berhad office Headquarters in KLIA 2, RedQ. In conducted this study, the sampling technique used is non probability sampling which is convenience sampling. The research method involved administering questionnaires survey to 90 employees. Our findings indicated that the result of Anova supported the research hypothesis. However, the result of regression analysis of coefficient which was employed to test the relationship between each organization success factors to the organizational success found that two variables which are leadership and organizational culture did not supported the research hypothesis. Based on the study results it is recommended that organizational leaders should directly engaged with employees and build positive culture in organization.